Literasi Keuangan Syariah dan Gaya Hidup Konsumtif: Studi Pengelolaan Keuangan Gen-Z Parepare - Ghufran Januar; Emily Nur Saidy; Besse Faradiba; Multazam Mansyur Addury (LPPM Universitas KH A. Wahab Hasbullah, 2026)
Generation Z is vulnerable to financial management issues due to trends in consumerist lifestyles, making it crucial to study financial literacy grounded in Sharia principles. The objective of this research is to analyze the influence of Sharia financial literacy and consumerist lifestyles on the financial management behavior of Generation Z in the city of Parepare. This study employs a quantitative approach with a total sample of 100 Generation Z respondents aged 18 and older. The sample size will be determined using the Slovin formula, and primary data will be collected by distributing questionnaires. The data will be analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via the SmartPLS software. The research findings demonstrate that Islamic financial literacy has a significant positive effect on financial management behavior, with a T-Statistic of 8.491 and a P-Value of <0.001. Conversely, a consumerist lifestyle has a significant negative effect, with a T-Statistic of 5.411 and a P-Value of <0.001. Simultaneously, both independent variables were found to have a significant effect, with an R² value of 0.553. This indicates that the model’s predictive power—or the proportion of variance in financial management behavior explained by the two independent variables—is 55.3%. It is concluded that improving understanding of Islamic financial literacy, accompanied by control over a consumerist lifestyle, is a key factor for Generation Z in developing healthy financial management behaviors that are in accordance with Islamic law.